The slag is converted into supplementary cementitious material by carbonation

By carbonizing the air-cooled blast furnace slag, the problem of difficulty in using non-reactive crystallized blast furnace slag in the prior art is solved, and the reactivity of the material and the environmental protection of the granulation process are improved, and the advantages of reducing CO2 emissions and improving cement strength are achieved.

CN116472256BActive Publication Date: 2025-03-28HEIDELBERG MATERIALS AG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180070696.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-16
Filing Date
2021-10-04
Publication Date
2025-03-28
Estimated Expiration
2041-10-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize non-reactive crystallized blast furnace slag as auxiliary gelling material, and traditional granulation methods have problems of high energy consumption and environmental pollution.

Method used

By carbonating the air-cooled blast furnace slag, it is converted into a reactive auxiliary gelling material, and the reactivity of the material is increased by using calcium carbonate and magnesium carbonate.

Benefits of technology

The conversion of non-reactive crystallized blast furnace slag into reactive materials is achieved, which reduces energy consumption and environmental pollution during the granulation process, and the carbonated slag has a contribution to enhancing the development of compressive strength in cement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116472256B_ABST
    Figure CN116472256B_ABST
Patent Text Reader

Abstract

The present invention relates to a supplementary cementitious material, a method for producing the supplementary cementitious material, a use of the supplementary cementitious material, a binder containing the supplementary cementitious material, a method for preparing the binder, and a use of the binder for manufacturing hydraulic building materials (such as concrete).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to an auxiliary cementitious material. In addition, the present invention relates to a method for producing an auxiliary cementitious material. The present invention also relates to the use of the auxiliary cementitious material. In addition, the present invention relates to a hydraulic binder, a method for preparing the binder and the use of the binder for manufacturing hydraulic building materials.

[0002] Cement is one of the most widely used products in construction. Therefore, reducing the demand for natural resources in cement manufacturing, both mineral raw materials and fuels, has been a goal for decades. Exchanging waste and by-products for raw materials and fuels is particularly beneficial, as is using such materials instead of cement clinker. For this reason, ground granulated blast furnace slag has been widely and successfully used as a supplementary cementitious material to obtain composite binders.

[0003] But not all slags are suitable as auxiliary cementitious material to obtain composite binders. Various types of slag are distinguished according to their origin. Blast furnace slag is produced as a rock melt at about 1500°C from accompanying iron ore minerals during reduction in a blast furnace, and slag forming agents are used as additives, such as limestone or dolomite. Slag from steel mills is also produced as a melt at about 1650°C during the processing of pig iron, sponge iron or scrap into steel. It is formed from oxidized secondary elements of pig iron and other metallic charges and lime or burned dolomite added for slag formation.

[0004] The difference between blast furnace slag and steel slag lies in their chemical composition and their basicity. Basicity refers to the weight ratio of certain oxides in the slag. For example, basicity B 1 , defined as CaO and SiO 2 The weight ratio of steel slag is usually in the range of 1.38 to 22.64. The basicity B of blast furnace slag 1 Usually in the range of 0.6 to 1.25. Basicity B 2 , also taking into account MgO, is typically in the range of 1.55 to 16.22, more typically 1.65 to 16.22, for steel slag and 0.7 to 1.6 for blast furnace slag. Basicity B 3 , also consider Al 2 O 3 , for steel slag is usually in the range of 1.08 to 3.17, more usually 1.25 to 3.17, and for blast furnace slag is 0.6 to 1.2. Basicity B 4 , defined as CaO and Fe 2 O 3 The weight ratio is usually in the range of 0.65 to 20.27 for steel slag, more usually 0.65 to 19.5, and 20 to 350 for blast furnace slag. Basicity B 1 , B 2 , B 3 and CaO and Fe 2 O3 B 4 Determined by the equation defined subsequently.

[0005] Blast furnace slag is a by-product of pig iron production. 3 ) compared to molten blast furnace slag, which has a lower density (~2.8 g / cm 3 ) and floats on the iron. This allows it to be discharged from the blast furnace separately from the iron.

[0006] Approximately 400 million tons of blast furnace slag are produced worldwide each year. Blast furnace slag has been studied and used for decades. There are two main types of blast furnace slag, air-cooled blast furnace slag and granulated (glassy) blast furnace slag. The latter is used in ground form as so-called ground granulated blast furnace slag (GGBS or GGBFS). Blast furnace slag contains various inorganic components, such as SiO 2 (30-42%), CaO (28-42%), MgO (1-11%), Al 2 O 3 (7-20%) and Fe 2 O 3 (0.2-3%), where the crystal structure of granulated (glassy) blast furnace slag is mainly X-ray amorphous, while the crystal structure of air-cooled blast furnace slag is essentially crystalline.

[0007] Granulated (glassy) blast furnace slag (as defined in EN197-1) is formed by rapid cooling of a melt and is formed in a blast furnace during the smelting of iron ore. It generally contains at least 2 / 3 (mass percentage) of vitreous solidified slag and exhibits hydraulic properties. According to EN197-1, such ground granulated blast furnace slag is mainly used as a cement component. In addition to the proven advantages in cement quality, such as low heat of hydration, good long-term stability, controlled alkali-silica reaction and acid resistance, according to EN197-1, granulated blast furnace slag is used in the cement industry to reduce the clinker content in standard cement and thus also reduce CO 2Discharge. It is known that the physical state of slag is fundamental to its cementitious properties. R. D. Hooton, The reactivity and hydration products of blast-furnace slag, Chapter 4, Department of Civil Engineering, University of Toronto, Toronto, Ontario, pp. 247-288, 1987 and R. Galibert, Glass content influence upon hydraulic potential of blast-furnace slag, National Slag Association, 184-2, 1-4 describe that the reactivity of cementitious binders decreases as the crystalline portion of slag increases.

[0008] In order to produce granulated (glassy) blast furnace slag, the molten slag is transported to a granulation plant. Blast furnace slag tends to cool rapidly and its viscosity increases, which impairs the granulation behavior and therefore the reactivity. The most common method for slag granulation is to quench it under high excess water and divide it into fine particles. Although it is an effective quenching method, water granulation has several disadvantages from the environmental and production point of view. The circulating process water must be recooled. In addition, the quenching water becomes contaminated by substances that have been leached from the slag, such as sulfur and sulfides. Such substances react with water to form hydrogen sulfide. In addition to potential air and water pollution, the slag obtained may have a high residual moisture content of up to 20% by weight and must be dried before grinding for gelling purposes, which means intensive energy input. In addition, the approximately 1.5 GJ / t of heat combined in the molten slag remains unused in this process.

[0009] One remedy could be granulation of the dry slag, which allows the use of this combined heat.Alternative granulation methods have also been developed, such as air granulation, but these cannot be used on a large scale because the cooling rates are too low.

[0010] The crystallized part of slag, such as the representative calcite group, calcite or anorthite, is inert for a longer period of 28 days or even 90 days, which is important for cement quality. For this reason, crystallized slag does not contribute significantly to the strength development of cement and is therefore undesirable.

[0011] Air-cooled blast furnace slag with a glassy fraction (substantially) below 66% has no or too little latent-hydraulic reactivity and is therefore often used in many countries as a substitute for stone and / or gravel for road construction. The X-ray amorphous fraction is often less than 15%. Such material is more suitable as an aggregate in concrete due to its inert properties and produces very high hardness.

[0012] However, increasing the reactivity of crystallized slag or its reactive phase content and using it in cement as a clinker substitute is more in line with the idea of ​​upcycling and the common zero waste concept. Such activation of crystallized materials would have enormous technical and ecological advantages.

[0013] F. et al., Minerals Engineering 41 (2013), 46-52, are concerned with the study of the behavior of the slag minerals calcite, calcite, calcite, calcite, gamma-silicate and tricalcium aluminate during dissolution. The results show that the nature and crystal structure of the minerals affect dissolution. At high pH values, the dissolution rate is generally slower.

[0014] A. Ehrenberg, Cement International, 4 (2012), Vol. 10, 65-79, deals with a comparison of the physical properties and reactivity of stored and fresh blast furnace slag. This study shows that if stored granulated blast furnace slag is properly handled, no adverse effects are expected on its performance as a potential hydraulic binder. Although blast furnace slag can bind to atmospheric or CO 2 High concentration of CO 2 , but the process is slow and has no significant practical impact. Studies have also shown that if not properly ground, the reactivity of blast furnace slag, and its contribution to cement and concrete strength, is reduced by carbonation. Characterizing the fineness of granulated blast furnace slag using the Blaine value can lead to misleading results if the granulated blast furnace slag has an increased ignition loss.

[0015] S.-Y. Pan et al., J. of Cleaner production, 137 (2016), 617-631, relate to the study of the physicochemical properties of different steel slag types that have been carbonated, such as basic oxygen furnace slag, electric arc furnace slag and ladle refinery slag.

[0016] Chen et al., J. of Cleaner production, 124 (2016), 350-360, related to the development of CO 2 The precursor material is basic oxygen furnace slag, which is subjected to a high gravity carbonation process. Basic oxygen furnace slag is a by-product from the processing of iron into steel. In addition, basic oxygen furnace slag has a basicity B of 3.3.1 .

[0017] US 2003 / 0131762 relates to slag cement mixtures wherein the mixture contains cupola slag, which is a by-product of iron casting in a cupola. The slag disclosed has been ground in air. However, naturally occurring CO 2 Not within the meaning of this invention.

[0018] Known proposals do not show a way to make air cooled blast furnace slag and materials of similar composition useful as supplementary cementitious material without requiring an undesirable amount of energy and / or economic effort. It is therefore an object of the present invention to provide a supplementary cementitious material in which non-reactive crystallized blast furnace slag has been converted into a reactive supplementary cementitious material.

[0019] It has now surprisingly been found that, after carbonation, air-cooled blast furnace slag and agglomerated slag or slag having a basicity B in a given range 1 -B 4 Thus, according to the present invention, the above-mentioned problems are solved by carbonating air cooling blast furnace slag, lump slag or other slag as auxiliary cementitious material.

[0020] Thus, the present invention relates to a supplementary cementitious material comprising Si, Ca, Mg, Al, Fe, wherein the X-ray amorphous portion is at least 15% by weight, based on the total weight of the supplementary cementitious material, and wherein the sum of the amounts of calcium carbonate and magnesium carbonate is at least 15% by weight, based on the total weight of the supplementary cementitious material obtained by carbonation of a precursor material having a basicity B ranging from 0.60 to 1.25 as determined by the amount of oxides measured by X-ray fluorescence (XRF). 1

[0021]

[0022] The present invention also relates to a method for producing an auxiliary cementitious material, the method comprising the following steps:

[0023] i) providing a precursor material, the precursor material comprising Si, Ca, Mg, Al, Fe, having a basicity B in the range of 0.60 to 1.25 1 , having an X-ray amorphous fraction of less than 66%, and having a D 90 ≤ 500 μm, preferably ≤ 200 μm, ii) carbonating the precursor material of step i) to provide a secondary cementitious material.

[0024] The X-ray amorphous fraction of the precursor material is increased by carbonation. In other words, for a particular precursor material, the X-ray amorphous fraction is lower than the X-ray amorphous fraction of the resulting secondary cementitious material. The term glassy shall herein refer to X-ray amorphous.

[0025] The invention also relates to the use of a supplementary cementitious material as defined above and below for the production of hydraulic building materials.

[0026] The invention also relates to a hydraulic binder comprising a supplementary cementitious material as defined above and below and cement.

[0027] The invention also relates to a process for producing a hydraulic binder as defined above and below, said process comprising

[0028] a) providing an auxiliary cementitious material as defined above and below,

[0029] b) blending the supplementary cementitious material of a) with at least one cement to provide a binder,

[0030] c) optionally blending the binder of b) with at least one admixture and / or additive to provide a hydraulic binder composition.

[0031] The invention also relates to the use of a binder as defined above and below for producing hydraulic construction materials, in particular concrete.

[0032] The carbonated slag (supplementary cementitious material) according to the present invention has at least one of the following advantages.

[0033] - Technically and energetically complex wet granulation and subsequent drying can be avoided.

[0034] -Can reduce CO 2 emission.

[0035] - Non-reactive crystallized blast furnace slag can be processed into reactive material without high energy requirements.

[0036] -The use of carbonated blast furnace slag as a clinker substitute in cement is possible and has several advantages.

[0037] - The method of the present invention represents CO 2 Exchange (CO 2 There are two reasons for the existence of a sink. Either from the atmosphere or from a source with a high CO 2 Concentration of exhaust gas CO 2 In addition, when carbonated blast furnace slag is used as a clinker substitute, this procedure again reduces CO 2 emission.

[0038] - The carbonated slag according to the invention has an increased contribution to the development of compressive strength in a mixture with cement, for example measured according to EN 450 (activity index).

[0039] The terms carbonation and carbonation are used synonymously.

[0040] To simplify the description, the following abbreviations commonly used in the cement field are used herein: H–H 2 O, C–CaO, ​​A–Al 2 O 3 , F–Fe 2 O 3 、M–MgO、S–SiO 2 and $–SO 3 The compounds are mostly named in pure form, without explicit reference to solid solutions, foreign ion substitution, impurities, etc., as is common in technical and industrial materials. As is known to those skilled in the art, the exact composition of the described phases may vary due to substitution with foreign ions. References to pure forms herein include such compounds unless explicitly stated otherwise.

[0041] Unless otherwise specified, the term "reactive" shall mean hydraulically reactive. Hydraulically reactive refers to the reaction of a compound with water or other water-containing compounds to form a hydrated phase, including the reaction of two or more compounds simultaneously.

[0042] In this article, clinker refers to a sintered product obtained by burning raw materials at high temperature and containing at least one hydraulic phase. Combustion refers to the change of one or more properties of the raw materials brought about by the supply of heat energy, such as chemistry, crystallinity, phase composition, spatial arrangement and bonding of lattice atoms. The raw materials can be a single material, but are usually a mixture. The raw materials are usually finely ground and then called raw materials. The raw materials may contain mineralizers, which are substances that reduce the temperature necessary for melting, and / or act as fluxing agents, and / or promote the formation of clinker, for example, by forming a solid solution or stabilization of the phase. The mineralizer can be part of the raw material components, or added as a separate component.

[0043] In the context of the present invention, cement is used to denote a material that, after being mixed with water to form a paste, is capable of developing mechanical strength by hydraulic reaction. Thus, cement refers to ground clinker or similar hydraulic phases obtained by other means, such as dicalcium silicate cement obtained by hydrothermal treatment. Binder or binder mixture refers to a material or mixture that contains cement and develops mechanical strength by hydraulic reaction with water, wherein the binder typically but not necessarily contains more components than cement. Thus, geopolymer binders, sulfated cements and composite cements are all referred to herein as binders. Binders are used by adding water or another liquid, usually also aggregates and optional admixtures and / or additives, to provide a paste that produces a construction element when hardened. Thus, in this article, paste refers to a mixture of binder and water, in particular but not limited to concrete and mortar.

[0044] Supplementary cementitious materials (SCM) in this article are defined as volcanic ash and / or latent hydraulic materials that can be used to replace a portion of cement in a binder. Potential hydraulic materials have a composition that allows hydraulic reaction when in contact with water, wherein typically requires an activator, so that it can harden within a technically feasible time. Activator refers to a substance that accelerates the hardening of latent hydraulic materials. It can be an additive, such as the product of sulfate or (hydrogen) calcium oxide and / or grinding clinker hydraulic reaction, for example, calcium silicate that releases calcium hydroxide during hydration. Volcanic ash materials are characterized by the content of reactive silicon dioxide and / or aluminum oxide, which form strength during hydration of clinker with released calcium hydroxide, and provide calcium silicate hydrate and calcium aluminate hydrate respectively. In practice, the boundary between latent hydraulic materials and volcanic ash materials is not clearly defined, and for example fly ash can be both latent hydraulic and volcanic ash, depending on their calcium oxide content. Therefore, the term SCM refers to latent hydraulic materials and refers to both volcanic ash materials. However, non-reactive materials or only slightly reactive materials, such as limestone, which substantially do not participate in the hydraulic reactivity, must be clearly distinguished from SCMs, which are sometimes summarized as mineral additions.

[0045] The supplementary cementitious material according to the invention is obtained by carbonation of a precursor material. Agglomerated slag, in particular air-cooled blast furnace slag, is used as a precursor material. An important parameter of such a slag is the so-called basicity, which describes the relative abundance of CaO (sometimes also CaO+MgO) and SiO. 2 Therefore, slag can be classified as "acidic" or "basic" slag, in which CaO and MgO are basic components and SiO 2 In other words, the basicity of slag is an empirical quantity that, in its simplest form, expresses the relative abundance of CaO and SiO in metallurgical slag. 2 Therefore, the concept of slag basicity B has nothing to do with chemical basicity, but is entirely based on the fact that CaO, together with the second components of slag (such as SiO 2) when reacting with water to form alkaline calcium hydroxide (Ca(OH) 2 ), where m refers to mass. Therefore, slag with a basicity B greater than 1 is called alkaline slag, and slag with a basicity B less than 1 is called acidic slag. 1 Defined as:

[0046]

[0047] It can also be combined with other components of slag (such as MgO, Al 2 O 3 , Fe 2 O 3 ), which are also assigned to the basic or acidic part. However, these must be weighted with a correction factor (k1 or k2) (m refers to mass) because, for example, MgO in slag does not have the same basic effect as CaO when reacting with water. Therefore, the basicity B 2 and B 3 Defined as:

[0048]

[0049] Another important factor regarding slag reactivity is the weight ratio of calcium oxide to iron oxide:

[0050]

[0051] The precursor material has a basicity B in the range of 0.60 to 1.25 1 In addition, the precursor material preferably has a basicity B in the range of 0.7 to 1.6 2 Furthermore, the precursor material has a basicity B in the range of 0.6 to 1.2. 3 Preferred precursor materials have a CaO / Fe ratio in the range of 20.00 to 350.00. 2 O 3 B 4 , preferably B 4 is at least 30, most preferably at least 50. Basicity B 1 , B 2 , B 3 and CaO / Fe 2 O 3 B 4 Determined by the equation defined above.

[0052] In the sense of the present invention, the basicity B of the steel slag 1 1.38 to 22.64, basicity B 2 1.55 to 16.22, more often 1.65 to 16.22, basicity B 31.08 to 3.17, more often 1.25 to 3.17, CaO / Fe 2 O 3 B 4 0.65 to 20.27, more often 0.65 to 19.5.

[0053] In the sense of the present invention, blast furnace slag has a basicity B of 0.6 to 1.25. 1 , 0.7 to 1.6 basicity B 2 , 0.6 to 1.2 basicity B 3 , CaO / Fe from 20 to 350 2 O 3 B 4 .

[0054] Typically, the precursor material has an X-ray amorphous portion of less than 66% by weight, based on the total weight of the precursor material, preferably an X-ray amorphous portion of ≤55% by weight, more preferably ≤40% by weight. In a particular embodiment, the precursor material has an X-ray amorphous portion of less than 15% by weight, based on the total weight of the precursor material. Another particular embodiment is a precursor material having an X-ray amorphous portion of less than 66% by weight, based on the total weight of the precursor material, preferably an X-ray amorphous portion of ≤55% by weight, more preferably ≤40% by weight, in particular less than 15% by weight, and / or having a basicity B in the range of 0.7 to 1.6 2 and / or a basicity B in the range of 0.6 to 1.2 3 .

[0055] In a preferred embodiment, the precursor material is air cooled blast furnace slag. The precursor material is preferably not steel slag. Steel slag is not a suitable precursor material due to the high iron content. The precursor material as described herein is obtained as known to those skilled in the art.

[0056] The precursor material generally contains Si, Ca, Mg, Al and Fe in the form of oxides as well as other compounds. Preferably SiO 2 The amount of is in the range of 25 to 45% by weight, and / or the amount of MgO is in the range of 3 to 15% by weight, and / or the amount of CaO is in the range of 20 to 45% by weight, and / or the amount of Al 2 O 3 The amount of Fe is in the range of 4 to 20% by weight. 2 O 3 The amounts are in the range of 0 to 2% by weight. Usually, these amounts are calculated as oxides, regardless of the actual compound present.

[0057] If the particle size distribution is not as expected, grind or pulverize and grind the precursor material. The particle size D 90Preferably ≤500 μm, more preferably ≤200 μm. 90 Preferably, it is in the range of 10 μm to 500 μm, more preferably 10 μm to 200 μm, especially 25 μm to 90 μm. The Rosin-Rammler slope n is preferably in the range of 0.6 to 1.4, especially 0.7 to 1.2. The crushing and / or grinding is carried out with devices and methods well known to those skilled in the art.

[0058] The supplementary cementitious material according to the present invention is obtained by carbonation of a precursor material, which will be described in more detail below. The resulting supplementary cementitious material according to the present invention generally comprises Si, Ca, Mg, Al, Fe in oxidized form and some Ca and Mg as carbonates. Preferably SiO 2 The amount of Mg calculated as MgO is preferably in the range of 3 to 15 wt%. The amount of Ca calculated as CaO is preferably in the range of 20 to 45 wt%. 2 O 3 The calculated amount of Al is in the range of 4 to 20 wt%. 2 O 3 The calculated amounts of Fe are in the range of 0 to 2 wt. %. These amounts are calculated as oxides and are based on no loss on ignition (LOI).

[0059] The auxiliary gelling material according to the present invention has an X-ray amorphous fraction of at least 15% by weight, based on the total weight of the auxiliary material. Preferably, the X-ray amorphous fraction is at least 25% by weight, based on the total weight of the auxiliary material.

[0060] Carbonation generally increases the amount of calcium carbonate and magnesium carbonate in the supplementary cementitious material according to the invention by at least 9% by weight, compared to the precursor material. 3 ) is preferably present in an amount of at least 15% by weight, more preferably at least 25% by weight, based on the total weight of the auxiliary cementitious material. Calcium carbonate and magnesium carbonate (CaCO 3 and MgCO 3 ) is preferably present in a total amount of at least 25% by weight.

[0061] The auxiliary cementitious material according to the present invention generally has a D 90 The auxiliary cementitious material according to the present invention preferably has a particle size distribution of 10 μm to 500 μm, more preferably 10 μm to 200 μm, and especially 25 μm to 90 μm. 90In a preferred embodiment, the auxiliary cementitious material according to the present invention has a Rosin-Rammler slope in the range of 0.6 to 1.4, especially 0.7 to 1.2.

[0062] The auxiliary cementitious material according to the present invention is obtained by carbonating a precursor material. The method for producing the auxiliary cementitious material comprises the following steps:

[0063] i) providing a precursor material, the precursor material comprising Si, Ca, Mg, Al, Fe, having a basicity B in the range of 0.60 to 1.25 1 , having an X-ray amorphous fraction of less than 66%, and having a D 90 Particle size distribution ≤500μm,

[0064] ii) carbonating the precursor material of step i) to provide a supplementary cementitious material.

[0065] Carbonation in the sense of the present invention does not include carbonation with naturally occurring CO by contact with air under atmospheric conditions. 2 Natural carbonation.

[0066] The precursor material described above is subjected to a carbonation step ii). The carbonation step is to obtain a carbon dioxide CO 2 A chemical reaction that binds to the precursor material. The auxiliary gelling material obtained includes carbonic acid and salts of alkali metals, alkaline earth metals and iron. Other carbonates may be present, but their amounts are not critical. In addition, since alkali metal carbonates (such as Li 2 CO 3 、Na 2 CO 3 or K 2 CO 3 ) are highly soluble in water, so they are not useful for long-term CO 2 In addition, due to the iron carbonate FeCO 3 It is a high-pressure and high-temperature phase, so only calcium carbonate and magnesium carbonate (CaCO 3 and MgCO 3 ) for CO 2 Therefore, the final CO 2 The storage potential can be calculated based on its calcium and magnesium content by the so-called Steinour (HH Steinour, "The Ultimate Products of the Carbonatization of Portland Cement", Res. Dept Portland Cem. Assn Unpubl., 1956.) formula:

[0067] CO 2(总) =0.785×(CaO-0.56CaCO 3 -0.7SO 3 )+1.091×(MgO-0.479MgCO 3 ),

[0068] Among them, CO 2(总) is the maximum theoretically achievable CO related to the dry mass 2 Sealing, CaO, CaCO 3 、SO 3 , MgO and MgCO 3 are the weight fractions of the corresponding oxides and phases.

[0069] In the carbonation reaction, CO 2 The partial pressure is, for example, in the range from 0.5 bar to 100 bar, preferably from 1 bar to 90 bar, in particular from 2 bar to 40 bar.

[0070] All pressures expressed herein are absolute pressures.

[0071] The carbonation can be carried out at discrete temperatures and discrete pressures. Alternatively, the carbonation can be carried out in a ramp mode, whereby the reaction temperature and / or CO 2 Pressure increases over time.

[0072] In a first embodiment, the reaction is carried out in only one reactor, whereby the reaction temperature and / or CO 2 The pressure is increased continuously or in several steps (incrementally), for example in 2, 3, 4 or more steps. Alternatively, the reaction can be carried out in a series of 2 or more reactors connected in series. In this case, in the flow direction of the reaction mixture, at least one downstream (further) reactor has a higher reaction temperature and / or a higher CO 2 content than the upstream (previous) reactor. 2 In a particular design, each downstream reactor has a higher reaction temperature and / or a higher CO 2 pressure.

[0073] Alternatively or additionally, when operating in one reactor as well as in several reactors, each reactor may have two or more reaction zones. In this case, each reactor may have two or more reaction zones with different temperatures and / or CO. 2For example, a different temperature, preferably a higher temperature than in the first reaction zone, can be set in the second reaction zone, or a higher temperature can be set in each subsequent reaction zone than in the previous reaction zone. In addition, for example, a different pressure, preferably a higher pressure than in the first reaction zone, can be set in the second reaction zone, or a higher pressure can be set in each subsequent reaction zone than in the previous reaction zone.

[0074] The carbon dioxide used in the process according to the invention can be used in gaseous, liquid, solid or supercritical form.It is also possible to use gas mixtures comprising carbon dioxide which are available on an industrial scale.

[0075] In a preferred embodiment, in step ii), CO 2 The concentration of CO is 10% to 100% by volume, especially 20% to 80% by volume. Therefore, it is preferred to react the precursor material with a mixture containing CO 2 The carbonation reaction occurs by contacting a gas or gas mixture, wherein CO 2 The concentration is preferably from 10% to 100% by volume, in particular from 20% to 80% by volume, based on the total volume of the gas or the gas mixture.

[0076] Typically carbon dioxide and precursor material are fed to the carbonation reaction, for example to step ii), in a molar ratio in the range of 0.2 to 20 moles, preferably 1 to 10 moles carbon dioxide per mole precursor material.

[0077] The carbonation in step ii) is preferably carried out at a temperature in the range of 20°C to 200°C, preferably 50°C to 180°C.

[0078] The carbonation time in step ii) is preferably in the range of 1 to 48 h, in particular 4 to 24 h.

[0079] In one embodiment, the carbonation is carried out in bulk. In another embodiment, the carbonation is carried out in the presence of a solvent, wherein the solvent is preferably water.

[0080] Another embodiment of the present invention is the use of the supplementary cementitious material as defined above and obtained by the process defined above for the manufacture of hydraulic building materials such as adhesives, concrete, mortars and special construction chemical mixtures, such as screeds and tile adhesives.

[0081] Preferably, the supplementary cementitious material according to the invention can be used as a major component in a composite binder. In another preferred embodiment, the supplementary cementitious material according to the invention can be used as a minor component in a composite binder. The supplementary cementitious material according to the invention can also be used as an additive to concrete and mortar, i.e., added during the manufacture of the wet mix, instead of being mixed with cement.

[0082] Another embodiment of the present invention is a binder comprising a supplementary cementitious material as defined above and obtainable by a method as defined above and a cement. The cement is preferably selected from the group consisting of Portland cement, Portland composite cement, calcium sulphoaluminate cement, calcium aluminate cement and dicalcium silicate cement. Preferred cements are those according to DIN EN 197. Particularly preferred are Portland cement, calcium sulphoaluminate cement and calcium aluminate cement.

[0083] In a preferred embodiment, the binder comprises:

[0084] - 1 to 88% by weight, based on the total weight of the binder, of an auxiliary cementitious material as defined above, based on the total weight of the binder, and

[0085] - 22 to 99% by weight of cement as defined above, based on the total weight of the binder.

[0086] For use, the binder is made into, for example, mortar or concrete by mixing with water. Typically, a water:binder weight ratio (w / b) of 1 to 0.1, preferably 0.75 to 0.15, most preferably 0.65 to 0.35 is used. For calculating w / b, the added SCM of the present invention and one or more optional additional SCMs are included in the amount of binder. The mortar or concrete typically also comprises aggregate and optional admixtures and / or additives.

[0087] Aggregate can be any known such aggregate. Sand and / or gravel of selected particle size is usually used. In some embodiments, lightweight aggregate is used, which is typically part of the aggregate, but can also be the only aggregate.

[0088] Admixtures are used to optimize properties such as setting time, hardening time, spreading, viscosity and uniformity, and to impart desired properties to the final concrete component, such as strength, flexural modulus, freeze-thaw resistance, etc. These admixtures are known per se and are used in their usual amounts. Admixtures that adjust the consistency while maintaining w / b in a suitable range are preferred admixtures, such as water reducers, plasticizers and superplasticizers. Useful water reducers, plasticizers and superplasticizers are, for example, but not exclusively, organic compounds having one or more functional groups selected from carboxylate, sulfonate, phosphonate, phosphate or alcohol functional groups. Other admixtures that affect processability are retarders. They are primarily directed to extending the time to maintain a specific consistency. Retarders slow down the setting and / or hardening of the binder paste. Suitable substances are, for example, but not exclusively, salts of phosphates, borates, Pb, Zn, Cu, As, Sb, lignin sulfonates, hydroxycarboxylic acids and their salts, phosphonates, sugars (sugars). In addition, admixtures which improve the durability of the concrete, such as air entrainers or hydrophobes, may be used. Admixtures may also be added to the binder if they are dry matter.

[0089] Additives are also usually included. Common examples are glass fibers, polymer fibers, cement kiln dust, silica fume, pigments. One or more of these can be used in the usual amounts. Additives are often added to the binder because most are dry matter.

[0090] Another embodiment of the present invention is a method for producing a hydraulic binder as defined above, said method comprising

[0091] a) providing an auxiliary gelling material as defined above,

[0092] b) blending the supplementary cementitious material of a) with at least one cement as defined above to provide a binder,

[0093] c) optionally blending the binder of b) with at least one admixture and / or additive and / or aggregate.

[0094] Another embodiment of the present invention is a hydraulic building material, such as concrete or mortar, comprising the supplementary cementitious material or binder as defined above.

[0095] The invention will be further illustrated below with reference to the following examples, without limiting the scope to the specific embodiments described. The present invention encompasses all combinations of described, particularly preferred features which are not mutually exclusive.

[0096] Unless otherwise specified, any amount in % or parts is by weight and, in doubtful cases, refers to the total weight of the composition / mixture involved. Characterizations as "about", "approximately" and similar expressions in relation to numerical values ​​are meant to include values ​​up to 10% higher and lower, preferably up to 5% higher and lower, and in any case at least up to 1% higher and lower, the exact values ​​being the most preferred values ​​or limits.

[0097] The term "substantially free" means that the particular material is not intentionally added to the composition and is present only in trace amounts or as an impurity. Unless otherwise indicated, the term "free" as used herein means that the composition does not contain the particular material, i.e., the composition contains 0% by weight of such material.

[0098] Example 1

[0099] To obtain lump slag for testing, glassy blast furnace slag having the composition determined by X-ray fluorescence spectroscopy (XRF) as given in Table 1 was heated to 1200°C in a laboratory furnace and then slowly cooled in the switched off furnace.

[0100] Table 1. Composition of slag

[0101]

[0102]

[0103] The obtained lump slag was ground in a ball mill to obtain a particle size of about 5000 cm according to Blaine. 2 / g specific surface area and D of ~28μm 90 The ground agglomerated slag was then carbonated in an autoclave (Pilotclav Type 3E / 31 Liter, Büchi AG) as follows. 200 g of agglomerated slag was mixed with water (water / solid ratio 0.5) and placed in a porcelain bowl in the autoclave. After the autoclave was closed, the temperature was raised to 80° C. Subsequently, CO was introduced. 2 A pressure of 40 bar was reached. This temperature and pressure were kept constant for 24 hours. After opening the autoclave, the sample was taken out and dried at 105° C. to constant weight.

[0104] Phases in bulk slag and carbonated slag were determined by QXRD. QXRD was performed using a diffractometer from Bruker with Cu anode, reflection geometry of 2θ = 4°-35°, increment of 0.02, at 25°C. Table 2 lists the phases determined by QXRD and their weight % amounts.

[0105] Table 2: Phases in carbonated slag

[0106]

[0107]

[0108] Thermogravimetric / differential thermal analysis (TG / DTA) was performed. The sample (8 to 22 mg) was placed in a platinum sample cup for measurement. A temperature program of 50 to 1000° C. at 10° C. / min and nitrogen flow was used. Figure 1 The TGA thermograms of uncarbonated and carbonated lump slag are shown. The comparison demonstrates that lump slag has CO 2 The carbonate content was found to increase by 24 wt% relative to the untreated sample.

[0109] Embodiment 2:

[0110] To measure the activity, all carbonated and uncarbonated samples from Example 1 were mixed with Portland cement. The evaluation was based on EN 450, a standard that describes a method for determining the contribution of fly ash to strength development. Therefore, 100% Portland cement was measured as a reference, and for the test, 25% Portland cement was replaced by the test material (lump slag or carbonated lump slag). The strength measurements and mortar composition were performed according to EN 196-1. The results are shown in Table 3, where the first two rows represent the sample composition, and the later rows list the measured strength and the activity index calculated therefrom. The last column represents the difference between carbonated slag and uncarbonated slag.

[0111] Table 3

[0112]

[0113]

[0114] The activity of lump slag is increased by carbonation. EN 450 specifies minimum levels of activity. According to the standard, fly ash should have an activity index of at least 75% after 28 days and at least 85% after 90 days. Lump slag achieves these targets after carbonation. In contrast, uncarbonated lump slag shows insufficient reactivity for use as SCM in composite binders, confirming the general wisdom in the field.

[0115] Example 3

[0116] In order to examine different carbonation conditions, the agglomerated slag from Example 1 was carbonated in an autoclave (Pilotclav Type 3E / 31 liter, Büchi AG) as follows. 50 g of agglomerated slag was mixed with water (water / solid ratio 2.0), placed in a porcelain bowl in the autoclave, and processed according to method A or method B described below. After opening the autoclave, the sample was removed and dried at 105° C. until a constant weight was reached.

[0117] Method A: After closing the autoclave, introduce N 2 The pressure in the autoclave was increased to 40 bar and then heated to 160°C. When temperature was reached, the autoclave was heated by introducing CO 2 The pressure in the autoclave was increased to 100 bar. This temperature and pressure were kept constant for 24 hours.

[0118] Method B: After closing the autoclave, N 2 The pressure in the autoclave was increased to 40 bar and then heated to 160° C. The temperature and pressure were kept constant. After 24 hours, the autoclave was heated to 160° C. by introducing CO 2 The pressure in the autoclave was increased to 100 bar. This temperature and pressure were kept constant for a further 24 hours.

[0119] Table 4 lists the phases identified by QXRD and their weight % amounts.

[0120] Table 4:

[0121]

[0122]

[0123] Table 5 shows the CO absorbed per dry mass of unreacted sample. 2 The amount, in % by weight, is determined by TG.

[0124] Table 5

[0125]

[0126] These results show that both Methods A and B yielded sufficiently carbonated products to be useful as SCMs, as evident from the phase composition.

Claims

1. A method for producing an auxiliary cementitious material, the method comprising the following steps i) providing a precursor material comprising Si, Ca, Mg, Al, Fe, having a basicity B1 defined as a weight ratio of CaO to SiO2 in the range of 0.60 to 1.25, having an X-ray amorphous fraction of less than 66%, and having a D 90 ≤ 500µm particle size distribution, wherein the precursor material is agglomerated slag, ii) carbonating the precursor material of step i) to provide a Supplementary Cementitious Material, wherein the X-ray amorphous fraction is at least 15 wt. % based on the total weight of the Supplementary Cementitious Material, and wherein the sum of the amounts of calcium carbonate and magnesium carbonate is at least 15 wt. % based on the total weight of the Supplementary Cementitious Material, and the X-ray amorphous fraction of the precursor material is increased by carbonation.

2. The process according to claim 1, wherein the carbonation in step ii) is carried out at a temperature ranging from 20°C to 200°C and / or at a pressure ranging from 1 bar to 100 bar.

3. The method according to claim 1, wherein the carbonation time in step ii) is in the range of 1 to 48 hours.

4. The method according to claim 2, wherein the carbonation time in step ii) is in the range of 4 to 24 hours.

5. The method according to claim 1, wherein the concentration of CO2 in step ii) is in the range of 10 to 100% by volume.

6. The method according to claim 2, wherein the concentration of CO2 in step ii) is in the range of 10 to 100% by volume.

7. The method according to claim 3, wherein the concentration of CO2 in step ii) is in the range of 20 to 80% by volume.

8. The method according to claim 4, wherein the concentration of CO2 in step ii) is in the range of 20 to 80% by volume.

9. The method of claim 1, wherein the precursor material has a CaO / Fe2O3 weight ratio of 30 to 350.

10. The method of claim 2, wherein the precursor material has a CaO / Fe2O3 weight ratio of 30 to 350.

11. The method of claim 3, wherein the precursor material has a CaO / Fe2O3 weight ratio of 30 to 350.

12. The method of claim 4, wherein the precursor material has a CaO / Fe2O3 weight ratio of 30 to 350.

13. The method of claim 5, wherein the precursor material has a CaO / Fe2O3 weight ratio of 30 to 350.

14. The method of claim 6, wherein the precursor material has a CaO / Fe2O3 weight ratio of 30 to 350.

15. The method of claim 7, wherein the precursor material has a CaO / Fe2O3 weight ratio of at least 50.

16. The method of claim 8, wherein the precursor material has a CaO / Fe2O3 weight ratio of at least 50.

17. The method of claim 1, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 18. The method according to claim 2, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 19. The method according to claim 3, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 20. The method of claim 4, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 21. The method of claim 5, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 22. The method of claim 6, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 23. The method of claim 7, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 24. The method of claim 8, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 25. The method of claim 9, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 26. The method of claim 10, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 27. The method of claim 11, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 28. The method of claim 12, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 29. The method of claim 13, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 30. The method of claim 14, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 31. The method of claim 15, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 32. The method of claim 16, wherein the precursor material has - less than 55% by weight of X-ray amorphous fraction, and / or - Basicity B2 in the range of 0.7 to 1.6 and / or Basicity B3 in the range of 0.6 to 1.2 。 33. A Supplementary cementitious material comprising Si, Ca, Mg, Al, Fe, wherein the X-ray amorphous portion is at least 15% by weight, based on the total weight of the Supplementary cementitious material, and wherein the sum of the amounts of calcium carbonate and magnesium carbonate is at least 15% by weight, based on the total weight of the Supplementary cementitious material obtained by the method of any one of claims 1 to 32, wherein the precursor material has a CaO / Fe2O3 weight ratio determined by the amount of oxides measured by X-ray fluorescence (XRF) ranging from 20 to 350.

34. The auxiliary cementitious material according to claim 33, wherein the auxiliary cementitious material has a D 90 Particle size distribution ≤500μm.

35. A supplementary cementitious material according to claim 33 or 34, wherein the precursor material is air cooled blast furnace slag.

36. Use of the supplementary cementitious material according to any one of claims 33 to 35 for producing a hydraulic building material, wherein the hydraulic building material is a composite adhesive, concrete, mortar, screed or tile adhesive.

37. A hydraulic binder, comprising the supplementary cementitious material according to any one of claims 33 to 35 and cement, wherein the cement is selected from at least one of Portland cement, calcium sulfoaluminate cement and calcium aluminate cement.

38. The hydraulic binder according to claim 37, comprising 1 to 88% by weight of the auxiliary cementitious material and 22 to 99% by weight of cement based on the total weight of the binder, and the sum of the contents of each component is 100% by weight.

39. A method for producing a hydraulic binder as claimed in claim 37 or 38, the method comprising a) providing an auxiliary cementitious material as claimed in any one of claims 33 to 35, b) blending the supplementary cementitious material of a) with at least one cement selected from Portland cement, calcium sulfoaluminate cement and calcium aluminate cement to provide a binder, c) optionally blending the binder of b) with at least one admixture and / or additive.

40. Use of the hydraulic binder according to claim 37 or 38 or the hydraulic binder obtained according to the method of claim 39 for producing hydraulic building materials.

41. The use according to claim 40, wherein the hydraulic construction material is mortar or concrete.

Citation Information

Patent Citations

  • Cupola slag cement mixture and methods of making and using the same

    US20030131762A1

  • Cupola slag cement mixture and methods of making and using the same

    US20020038617A1